Reinterpretation Reinterpretation of Surah At Taubah Verse 29 Against Acts of Terrorism Using Ma'na-Cum-Maghza Approach in Efforts to Prevent Islamophobia - Irbah, Zukhruful (UIN Sayyid Ali Rahmatullah Tulungagung, 2023)
Abstract: Islamophobia is a phenomenon of fear and threat to Islam. On January 21 2023, an incident occurred when the Koran was burned in Sweden. Islamophobia in this case is triggered by historical trauma due to what some members of extreme Islamic groups have done. This group tends to understand and adhere to the ideology of confrontation that the word